Assessment of Cognitive Components of Decision Making with Military Versions of the IGT and WCST. (September 2014) - Kennedy, Quinn; Nesbitt, Peter; Alt, Jon
The U.S. Army is focused on improving leader decision making, yet little is known as to how military officers develop optimal decision making. Two key components of optimal decision making are reinforcement learning and cognitive flexibility. Thirty-four military officers completed military versions of two standard cognitive assessments, the Iowa Gambling Test and the Wisconsin Card Sorting Task, while their eye movements were tracked. Results indicated that the military versions of these tasks successfully provided objective assessments of reinforcement learning and cognitive flexibility. Preliminary analyses of eye movements provide insights into the subjects' decision strategies. Training implications of the results are discussed.